The curricularization of extension in the context of distance education - Viegas , Cláudia Mara de Almeida Rabelo; Campos , Denise; Neiva, Rodrigo (Seven Editora, 2024)
Educational practices have evolved over time, above all, due to the challenges faced by educators, who constantly need to combine factors that involve human formation inserted in a context of an imperfect and contradictory society. DOI:https://doi.org/10.56238/sevened2024.015-022